2016
DOI: 10.1515/hf-2016-0043
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of liquefied wood waste for binding recycled wood particleboards

Abstract: Four types of industrial waste from wood processing, namely a mixed hardwood-softwood powder, pine and beech sawdust, and bark were liquefied and tested as binders for particleboards (PB) made of recycled wood. The liquefaction reaction was carried out at elevated temperature with a mixture of solvents from polyhydroxyl alcohols such as glycerine and propylene glycol, and p-toluenesulfonic acid as a catalyst. Then the liquefied woods (LWs) were characterized in terms of their suitability for PB production as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…With the use of bark as the adhesive filler, these negatives can be overcome. Bark in the liquefied form has been also applied as a UF modifier and tested as a binder for particleboards production (Janiszewska et al 2016) In addition to input raw materials, other key parameters that influence the final composite properties are the composition of adhesive mixtures, amount of adhesive, and the parameters of the pressing process (temperature, pressure, pressing time) (Igaz et al 2015(Igaz et al , 2016. Optimization of the pressing process can increase the manufacturing speed, decrease expenses, reduce energy, and lower emissions (Thoemen et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…With the use of bark as the adhesive filler, these negatives can be overcome. Bark in the liquefied form has been also applied as a UF modifier and tested as a binder for particleboards production (Janiszewska et al 2016) In addition to input raw materials, other key parameters that influence the final composite properties are the composition of adhesive mixtures, amount of adhesive, and the parameters of the pressing process (temperature, pressure, pressing time) (Igaz et al 2015(Igaz et al , 2016. Optimization of the pressing process can increase the manufacturing speed, decrease expenses, reduce energy, and lower emissions (Thoemen et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Corn flour improved mechanical performance and reduced formaldehyde emissions if added to UF [5]. A substitution up to 20% UF resin was reported using liquefied wood without impairing the mechanical properties of particleboards [6]. The co-condensation of UF with furfural proved to be feasible and resulted in reduced formaldehyde emissions at the expense of significantly increasing the necessary pressing temperatures [7].…”
Section: Introductionmentioning
confidence: 99%
“…Homogeneous catalysts (organic and inorganic alkalis, acids, and salts) are more active and popular than heterogeneous catalysts. Studied catalysts including acidic catalysts (hydrochloric acid, sulfuric acid, p-toluenesulfonic acid, oxalic acid), metallic salts, alkalis (sodium hydroxide), and acidic ionic confirmed that using strong acids as catalyst in the liquefaction process can cause corrosion of metallic equipment and environmental pollution compared with an alkali catalyst, but promotes higher efficiency of liquefaction [21,25,29].…”
Section: Introductionmentioning
confidence: 99%